The Influence of Public Services on Employee Performance at The BPKPAD Office, Binjai City - Antorio Ginting, Andi; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The aim of this research is to determine and analyze the influence of Public Services on Performance at the Binjai City BPKPAD Office. This research was carried out at the BPKPAD Office in Binjai City. The type of research is associative quantitative. The population in this study was 190 employees with ASN and honorary status in the General Section of the Binjai City BPKPAD Office. The sampling technique in this study used the Slovin technique, which consisted of 129 people. The research results show that Public Services have a significant influence on Performance as shown by the T-Statistic value of 5.664 > 1.656 and the P Value of 0.000 < 0.05. The adjusted R Square value is 0.195 or 19.50%, which means that public services have a low influence on employee performance, while the remaining 80.50% is influenced by other factors that have not been studied. This shows that improvements in Public Services can improve Performance at the Binjai City BPKPAD Office.